Probiotics for Celiac Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (31st October 2020) - Seiler, Caroline L.; Kiflen, Michel; Stefanolo, Juan Pablo; Bai, Julio César; Bercik, Premysl; Kelly, Ciaran P.; Verdu, Elena F.; Moayyedi, Paul; Pinto-Sanchez, Maria Ines
Abstract : INTRODUCTION: Many patients with celiac disease (CD) experience persistent symptoms despite adhering to the gluten-free diet. Different studies have assessed the use of probiotics as an adjuvant treatment for CD. We performed a systematic review and meta-analysis to evaluate the efficacy of probiotics in improving gastrointestinal (GI) symptoms and quality of life (QOL) in patients with CD. METHODS: We searched EMBASE, MEDLINE, CINAHL, Web of Science, CENTRAL, and DARE databases up to February 2019 for randomized controlled trials (RCTs) evaluating probiotics compared with placebo for treating CD. We collected data on GI symptoms, QOL, adverse events, serum tumor necrosis factor-α, intestinal permeability, and microbiota composition. RESULTS: We screened 2, 831 records and found that 7 articles describing 6 RCTs (n = 5, 279 participants) were eligible for quantitative analysis. Probiotics improved GI symptoms when assessed by the GI Symptoms Rating Scale (mean difference symptom reduction: 228.7%; 95% confidence interval [CI] 243.96–213.52; P = 0.0002). There was no difference in GI symptoms after probiotics when different questionnaires were pooled. The levels of Bifidobacteria increased after probiotics (mean difference: 0.85 log colony-forming units (CFU) per gram; 95% CI 0.38–1.32 log CFU per gram; P = 0.0003). There were insufficient data on tumor necrosis factor-a levels or QOL for probiotics compared with placebo. No difference in adverse events was observed between probiotics and placebo. The overall certainty of the evidence ranged from very low to low. DISCUSSION: Probiotics may improve GI symptoms in patients with CD. High-quality clinical trials are needed to improve the certainty in the evidence (see Visual abstract, Supplementary Digital Content 2, http://links.lww.com/AJG/B595 ).